Ye Hiwote tarik - Tekle Tsadik Mekuriya (Addis Ababa: : Eclips press, 2008)
An autobiography, of Takla Sadeq Makuriya, who held various senior postions in Emperor Haileselasie's government. The autobiography, however, covers from birth to the time of his resignation from government and eventual retirement in 1975. He passed on in July 2000.
Includes index.
In Amharic.
Keywords: Tekle Tsadik Mekuriya; Diplomats -- Ethiopia -- Biography; Ethiopia -- Politics and government -- 20th century